The Relationship of Environmental Uncertainty, AIS Efficiency and Energy Efficiency with Environmental and Operational Performance in Indonesia - Sajilan, Sulaiman; Ghani, Erlane K.; Maimunah, Siti; Lestari, Retno Martanti Endah (International Journal of Energy Economics and Policy, 2019)
Focusing on the current environmental era, the present study aims to evaluate the role of accounting and environment in driving the firm's performance. Therefore, the study is motivated to evaluate the specific relationship of energy efficiency, accounting information system efficiency and environmental uncertainty with business performance. The current study measures the empirical impact of the performance drivers on two vital domains of a firm's performance. The results of Partial Least Square structural equational modelling confirm that energy efficiency and accounting information system efficiency have a positive and significant impact on operational and environmental performance. Moreover, the results further suggested that environmental uncertainty have a negative and significant impact on operational and environmental performance in multinational firms of Indonesia. Keywords: Environmental uncertainty, energy efficiency, operational performance, environmental performance, Indonesia. JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8282